Leksikostatistik Bahasa Alune dan Wemale di Pulau Seram, Maluku : Lexicostatistics of Alune and Wemale Languages on Seram Island, Maluku - FARADIKA DARMAN (TOTOBUANG, 2022)
This study aims to identify and explain the kinship between Alune and Wemale languages ​​based on basic Swadesh vocabulary with lexicostatistical techniques. The method used in this research is qualitative and quantitative, and the research stages consist of three, namely data collection, data analysis, and presentation of the results of data analysis. The research data is in the form of a list of Swadesh vocabulary in the Alune and Wemale languages. Based on lexicostatistical calculations, the results show a kinship relationship between Alune and Wemale languages with the percentage of cognates or kinship words 96 And 103 non-kinship or non-cognitive vocabulary. Therefore, the conclusion is Alune and Wemale languages ​​are two related languages ​​and belong to the family or language family level. In addition, there are several forms of sound correspondence between Alune and Wemale languages, including b~p, e~a, ɛ~e, ø~y, k ~ø, r~d, a~u, p~k. Meanwhile, the forms of sound inheritance found include linear heritage, heritage with phoneme changes, the deletion of phonemes, the addition of phonemes, and with changes in phonemes accompanied by phonemes deletion.  Keywords: Alune, Wemale, lexicostatistics.